Mitigating Traffic Congestion: The Role of Intelligent Transportation Systems - Cheng, Zhi (Aaron); Pang, Min-Seok; Pavlou, Paul A. (Information Systems Research, 2020)
Mitigating Traffic Congestion: The Role of Intelligent Transportation Systems